Enhancing socio-economic justice and financial inclusion in Nigeria: The role of zakat, Sadaqah and Qardhul Hassan. Issue 3 (13th January 2020) - Zauro, Nurudeen Abubakar; Zauro, Nurudeen Abubakar; Saad, Ram Al Jaffri; Sawandi, Norfaiezah
Abstract : Purpose: The purpose of this paper is to discuss the roles of Zakat, Sadaqah and Qardhul Hassan within the context of the existing literature as major Islamic financial instruments for enhancing socio-economic justice amongst Muslims haves and have-nots as these enhance financial inclusion in Nigeria. Design/methodology/approach: The discussion in this paper is based on secondary sources such as the divine knowledge contained in the Qur'an, Hadiths and the existing literature, such as previously conducted empirical studies and Islamic world view ( Tawhidi epistemology). Findings: This paper implores Islamic societies to use Zakat, Sadaqah and Qardhul Hassan as instruments that encourages wealth redistribution that promotes efficient and effective wealth redistribution between haves and have-nots as part of the vicegerent ( khaliphah ) role between mortal being (human) and his immortal creator ( Allah ). This paper concludes by suggesting the use of these Islamic financial instruments as means to enhance socio-economic justice and financial inclusion in the Nigeria's Muslims' communities that are negatively affected by the high rate of financial exclusion and poverty as had been previously practiced in the Muslim world throughout the Islamic history. Research limitations/implications: This paper provides critical suggestions on the ways Zakat, Sadaqah and Qardhul Hassan will contribute significantly towards assisting Nigeria in achieving its vision of reducing the financial exclusion rate that is currently put at 41.6% to 20% by the year 2020 and may foster inclusive growth and sustainable development. However, the limitation is that it is a mare conceptual study, and the future researchers may subject it to the scientific test to offer empirical evidence regarding the roles of Zakat, Sadaqah and Qardhul Hassan towards closing the gap of financial exclusion in Nigeria. Originality/value: This paper contributes to the existing literature on the doctrine of the Islamic moral economy by recommending the adoption of Islamic financial instruments as tools for enhancing income redistribution and financial inclusion.